Finite element analysis of excavations in clay - Yap, Sien Mae. (2012)
Braced excavations are common methods for building underground structures. For design two-dimensional and three-dimensional finite element analyses are commonly used to assess the performance of the braced retaining wall system. Two-dimensional analysis is often preferred as it is simpler and less time consuming. The results however may not be as accurate as in plane strain the length of the excavation is ignored. Hence, the aim of the project is to compare when plane strain or a full three-dimensional.